PRINCIPLES OF CALCULATION OF THE PIEZOELECTRIC ELEMENTS WITH SURFACES PARTIAL ELECTRODES COVERING - Petrishchev, O. N.; Sharapov, V. M.; Sotula, Zh. V.; Bazilo, K. V. (Radio Electronics, Computer Science, Control, 2015)
The sequence of computational procedures, which allows when calculating transfer characteristics to use the full range of physical, mechanical and geometrical parameters of the piezoelectric element and the final value of the output electric impedance of the electrical signals generator, is proposed. The method, which allows you to perform the real situation adequate assessment of the connectivity effect of elastic and electric fields in the case of their arbitrary distribution in the volume of vibrating piezoelectric element, is proposed. The formulated complete set of boundary problems of technical electrodynamics and elasticity dynamic theory is the mathematical content of the energypower method of the piezoelectric elements physical state analysis in the regime of forced oscillations under the influence of the electrical energy external source. The proposed sequence of computational procedures can be recommended as a theoretical basis for characteristics calculating of the piezoelectric elements with partial surfaces covering by electrodes and microelectromechanical structures.